Genetic diversity and population structure of non-descript cattle in South African smallholder systems - Ramoroka, M. P.; MacNeil, M. D.; Neser, F. W. C.; Lashmar, S. F.; Makgahlela, M. L. (Frontiers in Genetics, 2025)
The genetic background and characteristics of South African smallholder cattle populations remain largely unknown. These cattle exhibit remarkable adaptability to challenging environments with minimal inputs from farmers, making them a valuable genetic resource for sustainable farming. This study aimed to genetically characterize non-descript cattle kept in smallholding systems using single-nucleotide polymorphism (SNP) markers. A total of 188 non-descript smallholder beef cattle were sampled from seven South African provinces; Eastern Cape (n = 27), Free State (n = 28), Gauteng (n = 13), KwaZulu-Natal (n = 29), Limpopo (n = 34), North West (n = 44) and Northern Cape (n = 10). In addition, samples were obtained from Afrikaner (n = 42), Bonsmara (BON; n = 46), Boran (n = 20), Brahman (n = 96), Drakensberger (n = 25), Hereford (n = 31), Holstein (HOL; n = 29), Nguni (n = 59) and Shorthorn (n = 35) to serve as reference populations. Quality control of the original SNP data removed less informative animals and SNPs, which resulted in a final data set consisting of 185 animals and 119,392 SNPs. Principal coordinate analysis, ancestry, and genomic diversity statistics revealed moderate to high levels of diversity within smallholder cattle and substantial relationship with commercial beef cattle (i.e., Afrikaner, Bonsmara, Brahman, Drakensberger, Hereford, Holstein and Nguni). In North West province, there was tendency towards greater influence of Bonsmara, whereas in KwaZulu Natal the cattle were more closely related to Holstein. The smallholder populations were shown not to be unique, likely due to indiscriminate hybridization with the commercial breeds. Among the provinces, estimates of observed heterozygosity (HO) ranged from 0.328 ± 0.001 to 0.395 ± 0.001, while expected heterozygosity (HE) ranged from 0.326 ± 0.001 to 0.389 ± 0.000. Inbreeding levels were low, with (mean ± standard error) per-province inbreeding coefficients (FIS) ranging from −0.023 ± 0.009 to 0.133 ± 0.0254. The low FROH (<0.05) across all populations indicate a more diverse population, which is less likely to express deleterious recessive traits. Estimates of the population differentiation fixation index (FST) indicated greater genetic distance between animals from KwaZulu natal and Gauteng provinces (FST = 0.083) and less distance between the animals from Eastern Cape and Free State provinces (FST = 0.010), suggesting a closer genetic relationship probably as a result of the proximity of the latter provinces and hence trans-boundary use of bulls. These findings suggest indiscriminate crossbreeding in smallholder cattle within and across the provinces of South Africa. The results provide foundational information for the transfer of technology for targeted breeding programs to smallholder farmers.